The Effect of Using English Animation Movies on the Speaking Ability of the Ninth Grade Students of MTs LPM Gema Kampar Kiri Hulu - Auliya, Anisa; Prawati, Atni; Masyhur, Masyhur (Jurnal Pendidikan Amartha, 2025)
The purpose of this research was to determine the improvement of students speaking ability after being taught through animation movies in the ninth grade of MTs Gema Kampar kiri Hulu. The researcher applied the pre-experimental method with one pre-test and post-test and the study lasted for six weeks. The research sample was Class IX of MTs Gema Kampar Kiri Hulu and the number of which was collected using purposive sampling techniques as many as 25 students in class IX. The techniques used to obtain the data are first, collecting data from the pre-test, second from the post-test and finally drawing conclusions based on the data obtained. In analyzing the collected data, t-test formula and normality test were used. From the analysis, the results showed that the Sig. value was 0.000 0.05. And the test scores are significant improvement, it means that once there is treatment by using animation movies it is effective and significantly influential in improving students speaking ability because animation movies can increase students’ interest in learning, it can facilitate students to understanding the material and strengthening memory because it displays audiovisual-based media.